The dark side of amyloid: PMEL, a natural amyloid in melanosome biogenesis - Marks, Michael (Henry Stewart Talks, 2008)
Functional amyloid, Amyloid fibrils in melanosome ultrastructure and formation, Pmel17 processing to a fibrillar form, Evidence that Pmel17 fibrils are amyloid, Role of multivesicular bodies in Pmel17 amyloid formation, Multivesicular bodies in amyloid formation by other substrates
Updated at 2020/05/15